The Effect of Ageing Treatment on Shape-Setting and Shape Memory Effect of a NiTi SMA Corrugated Structure - Yuanye Zhan; Liang He; Xiaofeng Lu; Xiaolei Zhu; Qing Chen (Advances in Materials Science and Engineering)
Ageing treatments were performed on Ti-50.53 at.% Ni shape memory alloy corrugated gasket (SMA-CG) units. The results of phase transition temperature, shape-setting, compression-resilience performance, and the shape memory effect (SME) of NiTi corrugated units were investigated. The experimental results show that high austenite finish temperatures could be achieved at 500°C and at 400°C aged for a long time, while the martensite finish temperatures were basically above room temperature. The peak value of the austenite finish temperature was found to be 500°C. The shape-setting result was better with the increase of ageing temperature and ageing time. It was stable when units were constrain-treated at 500°C and the ageing time was longer than 30 min. As the strain increases, the resilience rate of the unit decreased rapidly. The resilience rate decreased with the ageing process. Most of the aged units exhibited good SME when the maximum strain was less than 40%. There was the best recoverability when the ageing treatment was performed at 500°C for 60 min.